PENILAIAN KINERJA RECEPTIONIST PADA FRONT OFFICE DEPARTMENT DI HARRIS RESORT WATERFRONT BATAM - Indah Novita Sari; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The development of the hospitality business has led to increasingly fierce competition, especially in terms of marketing. Technological, social and cultural developments have led to many companies being established to achieve certain goals in meeting human needs. One of the companies engaged in the service sector is hospitality. In creating guest satisfaction, the hotel must be able to improve the quality of the hotel with employee performance. Good performance from hotel receptionists has a big role in service industries such as hotels. The purpose of this study is to analyze the performance assessment of receptionists in guest services at the front office department of Harris Resort Waterfront Batam. The type of research is descriptive qualitative. The subjects in the study were 3 people from the department and with reviews from several guests through one of the websites for Harris Resort Waterfront Batam. The results of this study were that the performance assessment of receptionists at the front office department of Harris Resort Waterfront Batam was in accordance with the theory of assessment. receptionist performance by FOM which includes good performance, good communication, good human relations, and good knowledge from a receptionist at Harris Resort Waterfront Batam. Keywords: Performance Assessment,Receptionist, Front Office,Harris Resort                 Waterfront Batam